Self-perception, knowledge, and awareness of halitosis among female university students - Bin Mubayrik, Azizah (Clin Cosmet Investig Dent, 2017)
BACKGROUND: Halitosis or oral malodor is defined as an unpleasant breath odor. It can become a serious problem affecting individuals’ social communication and self-confidence. Furthermore, it is a discomforting issue for the people around the person affected, because they consider it embarrassing to inform the person of the problem. AIM: This study was designed to measure self-perception, knowledge, and awareness of halitosis among female university students in Saudi Arabia. MATERIALS AND METHODS: A cross-sectional survey was implemented with 392 volunteer participants who responded to a questionnaire on their self-perception, knowledge, and awareness of halitosis. RESULTS: The response rate was 89.1% (392/440). Self-perception of halitosis was low (21.4%), whereas a larger percentage (78.1%) indicated noticing people with bad breath. Most participants (80.4%) thought that the gastrointestinal tract is the primary source of halitosis. Seventy-seven percent preferred using personal methods such as mouthwash and chewing gum to treat oral malodor. According to 82.1% of respondents, a dentist is the most appropriate professional to treat halitosis. CONCLUSION: The investigation revealed low self-perception and limited knowledge regarding halitosis. Therefore, the role of dentists in informing and educating their patients concerning oral malodor should be enhanced. Public education about the causes of and possible ways of managing bad breath should be increased.